Dual-controlled optogenetic system for the rapid down-regulation of protein levels in mammalian cells. Issue 1 (December 2018) - Baaske, Julia; Gonschorek, Patrick; Engesser, Raphael; Dominguez-Monedero, Alazne; Raute, Katrin; Fischbach, Patrick; Müller, Konrad; Cachat, Elise; Schamel, Wolfgang; Minguet, Susana; Davies, Jamie; Timmer, Jens; et al.
Abstract Optogenetic switches are emerging molecular tools for studying cellular processes as they offer higher spatiotemporal and quantitative precision than classical, chemical-based switches. Light-controllable gene expression systems designed to upregulate protein expression levels meanwhile show performances superior to their chemical-based counterparts. However, systems to reduce protein levels with similar efficiency are lagging behind. Here, we present a novel two-component, blue light-responsive optogenetic OFF switch ('Blue-OFF'), which enables a rapid and quantitative down-regulation of a protein upon illumination. Blue-OFF combines the first light responsive repressor KRAB-EL222 with the protein degradation module B-LID (blue light-inducible degradation domain) to simultaneously control gene expression and protein stability with a single wavelength. Blue-OFF thus outperforms current optogenetic systems for controlling protein levels. The system is described by a mathematical model which aids in the choice of experimental conditions such as light intensity and illumination regime to obtain the desired outcome. This approach represents an advancement of dual-controlled optogenetic systems in which multiple photosensory modules operate synergistically. As exemplified here for the control of apoptosis in mammalian cell culture, the approach opens up novel perspectives in fundamental research and applications such as tissue engineering.